Preference pravé a levé horní končetiny u primátů a její stabilita - Blažková, Veronika (Jihočeská univerzita, 2014)
Hand preference in primates was studied, especially in terms of comparing preferences for different actions and stability of these preferences in the life of an individual. A summary of researches on hand preferences in primates was made and commented.
The preference for the right and the left upper limb in primates and its stability
Keywords: preference končetin; stranové preference; preference; lateralita; primáti; stabilita